Extending the Contested Spaces of the Modern Kitchen. Issue 2 (February 2016) - Meah, Angela
Abstract: This essay seeks to broaden understandings of the domestic kitchen in the global North which consign its significance to the preparation or cooking of food, an activity assumed to be undertaken chiefly by women. Here, I take a social practice perspective, examining 'the kitchen' not as a monolithic physical 'site' (in the spatial sense) occupied primarily by women users, but as one where a range of practices cohere, reflecting multiple meanings and uses among those individuals who inhabit them. Exploring how the domestic kitchen has – over the last century – been conceptualised as a barometer of ideological dialectics, as an orchestrating concept and as the symbolic heart of the home, I reveal how this most humble of domestic spaces is both material and symbolic, figurative and substantive, rendering it a serious – but often neglected – object of academic inquiry.